2021
DOI: 10.1016/j.jse.2020.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Stand-alone coracoclavicular suture repair achieves very good results in unstable distal clavicle fractures at a minimum follow-up of 1 year

Abstract: Background: The treatment of unstable (Neer type IIB and V) extra-articular distal clavicle fractures remains challenging, especially when encountering a small lateral fragment which does not allow for sufficient screw purchase. It was the purpose of this study to present the clinical and radiologic outcome of a consecutive series of patients treated by a stand-alone coracoclavicular stabilization using a so-called cow-hitch technique with a suture anchor. Methods: Nineteen patients were treated with a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Complementary to a clinical case series, 13 the present study now also provides biomechanical evidence that the use of the occasionally irritating clavicular button is dispensable when using the cow-hitch suture technique and, thus, the number of secondary surgeries can be reduced in patients with distal clavicle fractures.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Complementary to a clinical case series, 13 the present study now also provides biomechanical evidence that the use of the occasionally irritating clavicular button is dispensable when using the cow-hitch suture technique and, thus, the number of secondary surgeries can be reduced in patients with distal clavicle fractures.…”
Section: Discussionmentioning
confidence: 52%
“…Compared with the original description, 14 the cow-hitch technique was later modified by using a suture button to combat the risk of anchor pullout through a larger and cortical rather than cancellous implant-bone interface and avoid the risk of suture breakage at the anchor eyelet. 6 In addition, fixation in this manner is assumed to be more independent of bone quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have suggested that reconstructing ligament stability can shorten the CC distance and enhance the fixation stability of clavicle fractures [ 9 , [13] , [14] , [15] ]. However, others believe that there is no significant difference in the final fracture healing effect and shoulder function between treatments using plate fixation alone and plate fixation with additional CC ligament augmentation [ 10 , 11 , 16 , 17 ]. Almost all reports have evaluated Neer type V and II fractures together as unstable distal clavicle fractures or only Neer type II fractures.…”
Section: Introductionmentioning
confidence: 99%